Analysis of Traffic Infrastructure in the Town of Kutina - Vurdelja, Joso; Žmegač, Davor; Rajković, Valentino (Promet - Traffic&Transportation)
The analysis of the current condition regarding the trafficinfrastructure of the town of Kutina it is possible to concludethat in some elements it fully satisfies the needs of its users,whereas in some other elements there are certain divergences. Itis specially emphasised that a significant part of the trafficproblems of Kutina cannot be solved in a good and permanentmanner unless the basic guidelines in the urban planning areadopted and the facilities for public purposes are built, meaningfirst of all the market and similar facilities for public use.The good location of such facilities changes the whole conceptof the urban traffic flows and the co-ordinated planning resultsin permanent and good traffic solution of the whole traffic networkof Kutina.In order to harmonise the existing condition of the trafficinfrastructure with the current and planned needs of the citizensof Kutina, the social community should cany out detailed traffie research and insure adequate financial means for this purposefrom the budget.